2019
DOI: 10.1016/j.scitotenv.2019.03.398
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of land use on an insectivorous tropical bat: The importance of mercury, physio-immunology and trophic position

Abstract: Deforestation, agricultural intensification, and habitat homogenization are critical threats to biodiversity in Southeast Asia. Limited information is available on the trophic and physiological responses of tropical animals to these environmental changes. The wrinklelipped free-tailed bat Chaerephon plicatus is a cave roosting species that is experiencing population declines across Southeast Asia, where landscapes have been drastically modified.In our study site in central Thailand, we tested the hypothesis th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 70 publications
2
26
0
Order By: Relevance
“…We observed a clear elevation in haptoglobin, an acute phase protein of the innate immune response, following the LPS challenge. Haptoglobin has only been measured in a few bats, which showed a clear elevation in response to fungal 34 and human stress 38 . In both free and captive bats, haptoglobin continuously increased during the entire period of the study, as also observed in other mammals 64 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We observed a clear elevation in haptoglobin, an acute phase protein of the innate immune response, following the LPS challenge. Haptoglobin has only been measured in a few bats, which showed a clear elevation in response to fungal 34 and human stress 38 . In both free and captive bats, haptoglobin continuously increased during the entire period of the study, as also observed in other mammals 64 .…”
Section: Discussionmentioning
confidence: 99%
“…Haptoglobin concentration To measure the concentration of haptoglobin, the standard procedure of the commercial kit "PHASE"TM Haptoglobin Assay (Tridelta, Maynooth, Ireland) was followed, which was already used in other bat species 34,38 . Briefly, after diluting the plasma samples (1:2) with PBS, haemoglobin was added.…”
Section: Bmentioning
confidence: 99%
See 2 more Smart Citations
“…Iron‐binding glycoprotein TF helps maintain iron homeostasis, which is altered during infections and which influences modulation of innate immune defences and prevention of pathogen survival (Ganz & Nemeth, 2015). It is functionally similar to haptoglobin, another important APP in bats (Costantini, Czirják, Bustamante, Bumrungsri, & Voigt, 2019; Fritze et al., 2019), which has been identified in the wing tissue transcriptome of WNS positive M. lucifugus (Field et al., 2015). As a major protease inhibitor, A2M is involved in regulating inflammatory processes by scavenging defensins and inhibiting proteases of host and nonhost origin, which protects inflamed tissues against excessive damage (Rehmann, Ahsan, & Khan, 2013).…”
Section: Discussionmentioning
confidence: 99%